Manual de monstrologia : psicanálise e cisgeneridade (e uma monstrotopia possível) - Silva, Lucas Guerra da (2022)
The realization that cisgender people are authorized for some reason to make thousands of comments below any news shared by journalistic portals on Facebook, which talked about transsexuality, gave me the insight to start my research on this very ordinary phenomenon. This thesis tells which affections, meanings and imaginaries are behind (in the unsaid) of what is said within a few characters typed and published as opinions massively liked and fed back, within these legitimate places of habitation of human people in our cultural dynamics contemporaries, the codes-territory, that is, the platforms of social networks, in our time: post-humanity. What is so destabilizing, in so many people at the same time, to the point of making them translate thoughts and persecutory anxieties into written words, and words loaded with affection, building spontaneous bubbles of content feedback that aim to eliminate the theme itself ? Here there is a critique of psychoanalysis, after all, it is historically a device for reproducing the naturalization of cisgenderism and heteronormativity, from the formulation of the idea of a psychosexual development within an Oedipal family, with its father and mother figures under the economy of maternal function and paternal function, which from the incestuous duality and later castrating triangulation precisely represent health (in the case of a resolution of the Oedipus complex) or disease (in the case of failures). To carry out this denunciation of a cisgender and heteroterrorist psychoanalysis, I chose an illustrative cut, and invoked to dialogue with me the cisgender psychoanalyst Joan Riviere, an important thinker who makes a theoretical bridge between the Freudian and Kleinian schools. His interpretations, as an illustration for several psychoanalytic texts that also discuss gender and sexuality issues, are invested with an essentialism never questioned, which, when tensioned, mobilizes the circular return of its explanation to psychoanalysis itself and its interpretive technique, instead of actually listening the emotional experience through the words of the one who is telling it. The same is done by cisgender people on social media: they reposition themselves without listening to the experiences of others, and they want the psychological sciences (here Psychoanalysis and Psychiatry too) to be the repository of what they understand to be abnormal. I then had to reflect that, if Psychoanalysis does not actually describe the phenomena it classifies, but actually constructs the phenomena with its words and interpretations; then, she forges what she herself pursues as illness; it makes something that could be familiar, something from the field of the disease that demands clinical management to return to a supposed stability, which would be cisgenderness. Hence to point out that the psychological sciences that work with the strangeness of certain phenomena that are determined and interpreted through theoretical positions that do not correspond to the emotional experiences of the classified people (after all, it was not trans people who said they were mentally disturbed, or abnormal, but people who generically understand themselves as “normal”), these sciences, produce their manuals of monsterology. They deposit the abnormal at the edge or beyond the boundary determined by normality, and then operate their surveillance and control techniques. The manuals of monsterology, in turn, are the denunciation of a functioning that I called “social lupus”, when the set of surveillances estranges what they themselves produced as discourse, and then they attack. To overcome this problem, I built a possible and displaced refuge from the here-now, “Monstrotopia”, from a speculative fabulation, which tensions the psychoanalytic interpretation, and kinship.